2019
DOI: 10.3390/ijerph16173219
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Photocatalysis and Adsorption for Simultaneous Removal of Hexavalent Chromium and Methylene Blue by g-C3N4/BiFeO3/Carbon Nanotubes Ternary Composites

Abstract: A novel graphite-phase carbon nitride (g-C3N4)/bismuth ferrite (BiFeO3)/carbon nanotubes (CNTs) ternary magnetic composite (CNBT) was prepared by a hydrothermal synthesis. Using this material, Cr(VI) and methylene blue (MB) were removed from wastewater through synergistic adsorption and photocatalysis. The effects of pH, time, and pollutant concentration on the photocatalytic performance of CNBT, as well as possible interactions between Cr(VI) and MB species were analyzed. The obtained results showed that CNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The composites of pristine BiFeO 3 with other semiconductor materials are also studied and used for photocatalytic pollutant degradation, which includes different photocatalysts, viz., BiFeO 3 /Bi 25 FeO 40 , BiFeO 3 –Ti 3 C 2 , BiFeO 3 –ZrO 2 , and BiFeO 3 –TiO 2 . Some ternary and quaternary composites, viz., Ag 3 PO 4 /Bi 25 FeO 40 /GO, Ag 2 CrO 4 /Ag/BiFeO 3 @RGO, Ag/BiPO 4 /BiOBr/BiFeO 3 , and g-C 3 N 4 /BiFeO 3 /CNTs are also reported for the degradation of different organic pollutants. As earlier discussed about the defected perovskites, Chen et al have prepared oxygen-deficient BiFeO 3 by high-pressure and high-temperature treatment of pristine BiFeO 3 NP under H 2 atmosphere .…”
Section: Energy and Environmental Applicationsmentioning
confidence: 94%
“…The composites of pristine BiFeO 3 with other semiconductor materials are also studied and used for photocatalytic pollutant degradation, which includes different photocatalysts, viz., BiFeO 3 /Bi 25 FeO 40 , BiFeO 3 –Ti 3 C 2 , BiFeO 3 –ZrO 2 , and BiFeO 3 –TiO 2 . Some ternary and quaternary composites, viz., Ag 3 PO 4 /Bi 25 FeO 40 /GO, Ag 2 CrO 4 /Ag/BiFeO 3 @RGO, Ag/BiPO 4 /BiOBr/BiFeO 3 , and g-C 3 N 4 /BiFeO 3 /CNTs are also reported for the degradation of different organic pollutants. As earlier discussed about the defected perovskites, Chen et al have prepared oxygen-deficient BiFeO 3 by high-pressure and high-temperature treatment of pristine BiFeO 3 NP under H 2 atmosphere .…”
Section: Energy and Environmental Applicationsmentioning
confidence: 94%
“…The findings demonstrated that CNTs could significantly improve the photocatalytic efficiency of the prepared composite by reducing the rate of electron-hole pair recombination. The rates of elimination of Cr 6+ after 5 h of adsorption by CNBT were 98% [90]. Zhu et al prepared nano nickel particles implanted in Nitrogen-doped CNTs with porous biochar support (Ni-N-K-C).…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…The poor result of the p-g-CN/rGO/BiVO 4 structure is likely due to the formation of a typical type II heterojunction facilitated by the increased charge mobility and intermediate charge states introduced by rGO as well as the combined shadowing effects from BiVO 4 and rGO. [8,52,53] The layering of the rGO and BiVO 4 sheets on the surface of p-g-CN may have also limited the mass transport at the surface.…”
Section: Photocatalytic Co 2 Reductionmentioning
confidence: 99%